Effects of fine-needle aspiration biopsy (FNAB) nodule depth on pain score. (August 2016) - Toman, H.; Ozkul, F.; Erbag, G.; Erbas, M.; Simsek, T.; Adam, G.; Arik, M.; Asik, M.
Abstract Purpose Fine-needle aspiration biopsy (FNAB) of the thyroid is generally a well-tolerated procedure associated with weak levels of pain. However, pain may be very intense in some patients. The cause for the pain in these patients has not been identified. The hypothesis of this study is that there is a likely relationship between pain level and nodule depth during FNAB. Materials and methods Included in the study were 98 patients with euthyroid nodular goiter who underwent FNAB. When ultrasound guided thyroid fine-needle aspiration biopsy was performed findings such as the distance of the nodule to the skin, the size of the nodule, visual analogue scale (VAS) score values were recorded. Findings The distance of nodule to skin and nodule size was measured, respectively, as 10.7 ± 2.8 mm and 21.7 ± 8.6 mm. Mean VAS score was 36 ± 16. FNAB-related pain was correlated with the nodule depth (r = 0.43, p < 0.001). In the logistic regression analysis, we also found that high VAS score class was effected by only nodule depth (B = −1.619; OR 1.287; CI 1.057–1.565, p < 0.05). Conclusion Our results show that pain increased significantly during FNAB in patients who had more deeply situated nodules. Local anesthetic methods may be recommended for these patients.